Mapping valence band and interface electronic structure changes during the oxidation of Mo to MoO3 via MoO2 and MoO3 reduction to MoO2: A NAPPES study - Reddy, Kasala Prabhakar; Mhamane, Nitin B.; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2018)
Tuning the surface energetics, especially work function (phi) of the materials, is of a great deal of interest for a wide range of surface- and interface-based devices and applications. How the phi of a solid surface changes under the reaction conditions is of paramount interest to the chemists, particularly in the areas of surface dependent phenomena such as, catalysis and electrochemistry. In the present study, by using the valence band and core-level photoelectron spectroscopy, surface-electronic changes from Mo to MoO3 via MoO2 was studied under relevant near-ambient pressure (NAP) and high temperature conditions. A very significant change in phi from Mo to MoO3 was observed and it is well corroborated with the changes in gas-phase vibrational features of O-2 in both near-ambient pressure ultraviolet photoelectron spectra (NAPUPS) as well in NAP X-ray photoelectron spectroscopy. Reversible changes in the electronic structure is observed when MoO3 was reduced in H-2 to MoO2. On the basis of the extent of oxidation/reduction of MoOx NAPUPS has shown, one or two additional peaks in the band gap at 0.6 and 1.6 eV below the Fermi level. Mo5+ features are identified in the VB and in the Mo 3d core levels with distinct features. Mo5+ features are also stable and essential to bridge MoO2 and MoO3 layers, and their co-existence. In addition, characteristic changes in Mo 4d and O 2p features observed from Mo to MoO3 and well corelated to the band gap of MoO3. Oxidation and reduction propagate from the surface to bulk; indeed, this has significant implications in surface-dependent phenomena. The present study demonstrates (a) the uniqueness of NAPUPS in identifying the subtle to large changes in the electronic structure on solid surfaces under common oxidation and reduction (in general, under reaction) conditions, and (b) relevance of NAPUPS to all surface dependent phenomena, such as catalysis and electrochemistry.

Molybdenum carbide catalyst for the reduction of CO2 to CO: surface science aspects by NAPPES and catalysis studies - Reddy, Kasala Prabhakar; Dama, Srikanth; Mhamane, Nitin B.; Ghosalya, Manoj K.; Raja, Thirumalaiswamy; Satyanarayana, Chilukuri V.; Gopinath, Chinnakonda S. (Dalton Transactions, 2019)
Carbon dioxide is a greenhouse gas, and needs to be converted into one of the useful feedstocks, such as carbon monoxide and methanol. We demonstrate the reduction of CO2 with H-2 as a reducing agent, via a reverse water gas shift (RWGS) reaction, by using a potential and low cost Mo2C catalyst. Mo2C was evaluated for CO2 hydrogenation at ambient pressure as a function of temperature, and CO2 : H-2 ratio at a gas hourly space velocity (GHSV) of 20 000 h(-1). It is demonstrated that the Mo2C catalyst with 1 : 3 ratio of CO2 : H-2 is highly active (58% CO2 conversion) and selective (62%) towards CO at 723 K at ambient pressure. Both properties (basicity and redox properties) and high catalytic activity observed with Mo2C around 700 K correlate well and indicate a strong synergy among them towards CO2 activation. X-ray diffraction and Raman analysis show that the Mo2C catalyst remains in the beta-Mo2C form before and after the reaction. The mechanistic aspects of the RWGS reaction were determined by near-ambient pressure X-ray photoelectron spectroscopy (NAPXPS) with in situ generated Mo2C from carburization of Mo-metal foil. NAPXPS measurements were carried out at near ambient pressure (0.1 mbar) and various temperatures. Throughout the reaction, no significant changes in the Mo2+ oxidation state (of Mo2C) were observed indicating that the catalyst is highly stable; C and O 1s spectral results indicate the oxycarbide species as an active intermediate for RWGS. A good correlation is observed between catalytic activity from atmospheric pressure reactors and the electronic structure details derived from NAPXPS results, which establishes the structure-activity correlation.

Gas-solid interactions with reactive and inert gas molecules by NAPUPS: can work function be a better descriptor of chemical reactivity? - Ghosalya, Manoj Kumar; Reddy, Kasala Prabhakar; Mhamane, Nitin B.; Ranjan, Ravi; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2020)
The gas-phase vibrational spectra of reactive (H(2)and O-2) and inert gases (N(2)and Ar) have been studied by near-ambient pressure (NAP) ultraviolet photoelectron spectroscopy (NAPUPS) up to 0.3 mbar pressure. The results obtained are divided into two parts and discussed. In the first part, the photoelectron spectra of monoatomic Ar and some homonuclear diatomic molecules, such as H-2, O-2, and N-2, have been recorded by NAPUPS and the effect of pressure on their energy position has been studied. It has been demonstrated that NAPUPS could be an essential tool to determine the intermolecular or interatomic interactions. In the second part, we have evaluated the influence of different solid surfaces on the binding energy (BE) position, the pattern of the vibrational features of diatomic N(2)molecules, and the first atomic levels (3p(3/2)and 3p(1/2)) of monoatomic Ar. It has been observed that with a change in the (electronic/chemical) nature of the surface, the BE of the above features also changes and reflects the change in the work function (phi) of the material. It is to be noted that Ar is an inert/noble gas and N(2)is the most stable molecule, and the above changes observed underscore that they can be employed as probe atoms/molecules to explore even the minor changes that occur on a solid surface due to a variety of reasons. Further, if the solid surface undergoes any chemical/electronic changes due to gas-solid interaction, such as oxidation/reduction, the phi of the surface changes again; this highlights the precise identification of the changes that occur under the reaction/measurement conditions. Therefore, the change in the BE of the gas-phase features can be used to determine even the minor changes in the phi of solid surfaces during the reaction or due to the reaction. The present findings have implications in probing the surface changes that occur in any surface-dependent phenomena, such as heterogeneous catalysis, electrochemistry, and materials that are predominantly controlled by surface contribution, such as layered (2D) materials, nanomaterials.

Electronic structure evolution from metallic vanadium to metallic VxOy: a nappes study for o2+v gas-solid interaction - Ranjan, Ravi; Mhamane, Nitin B.; Kolekar, Sadhu K.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2022)
Gas-solid interactions between molecular oxygen and metallic vanadium surfaces and the systematic evolution in the electronic structure of vanadium oxide (VOx) surfaces have been explored in the present work by near-ambient pressure photo-electron spectroscopy (NAPPES). The current article studies the evolution of various oxides of vanadium as a function of partial pressure of O2 (ultrahigh vacuum to 1 mbar), temperature (298- 875 K), and the exposure time to oxygen (up to 18 h). Valence -band (VB) and core-level spectral measurements recorded with UV (He-I = 21.2 eV) and Al K alpha (1486.6 eV) photons, respectively, show interesting changes. (1) Oxidation is limited to the top layers of vanadium at 298 K and up to a partial pressure of 1 mbar O2. About 50% of vanadium gets oxidized, and the remaining amount exists as metal within the top 10 nm. (2) Metallic vanadium disappears above 625 K, and it is predominantly oxidized to a mixture of V4+ and V5+ oxidation states at a 0.1 mbar partial pressure of O2. Points 1 and 2 suggest the predominantly thermodynamically controlled nature of vanadium oxidation through oxygen diffusion into the subsurface and bulk layers. (3) The Fermi-level (EF) feature observed first at >= 725 K at a 0.1 mbar O2 pressure demonstrates the formation of metallic VO2; however, its metallic nature is preserved even at ambient temperature due to interweaving nanodomains of VOx with VO2. (4) Only partial conversion of surface layers to V5+ (V2O5) along with VO2 and V2O3 (within the probing depth of 8-10 nm by near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS)) was observed even after prolonged heating (18 h) in 1 mbar O2 pressure. (5) The nature of the surface changes between metal and semiconducting/ insulator oxides is substantiated by the observation of changes in work function (phi) and EF features. Typical VB features and Fermi intensity of V-metal and vanadium oxides were observed, and the results were corroborated with core-level and VB spectra. The present results extend the capabilities of NAPPES to explore the electronic structure evolution as a function of reaction conditions and underscore its relevance to areas such as heterogeneous catalysis and sensing.

Possible fine-tuning of methane activation toward C2 oxygenates by 3d-transition metal-ions doped nano-ceria-zirconia - Kanungo, Subhashree S.; Mishra, Abhaya Kumar; Mhamane, Nitin B.; Marelli, Udaya Kiran; Kumar, Dharmesh; Gopinath, Chinnakonda S. (Inorganic Chemistry, 2022)
In this work, we demonstrate a simple sol-gel technique to prepare metal-ion(s)-doped ceria-zirconia solid solution for efficient catalytic methane activation. The cation -depicting formula units are Ce0.80Zr0.20 (CZ), Ce0.79Zr0.20M0.01 (CZM), and Ce0.79Zr0.20M0.005M10.005 (CZMM1) (M and M1 = V, Mn, Fe, Co, and Cu), employed for undoped, mono-metal-ion -doped, and bi-metal-ion-doped solid solutions, respectively. Methane activation with Mn, Fe, Cu mono-metal-ion-doped CZ favors the C1 product, while CZCo assists C-C coupling with the formation of acetaldehyde. On the other hand, the Co-and Fe -doped bi-metal-ion combination catalyst (CZCoFe) shows significant ethanol but predominant formic acid formation. This is further promoted by the Co + V bi-metal-ion combination (CZCoV) catalyst, and it shows ethanol as the major product along with methyl hydrogen peroxide, methanol, and formic acid as minor products. An impressive ethanol yield of 93 mu mol/g h with 76% selectivity obtained with the CZCoV catalyst is at par with that obtained with noble-metal-based catalysts under comparable reaction conditions. When Co and V content was increased two and four times from 0.005 to 0.01 and 0.02, ethanol yield increased at the expense of formic acid. The 213 mu mol/g h ethanol yield (86% selectivity) observed with Ce0.76Zr0.20Co0.02V0.02 is probably the highest observed. The partial oxidation of CH4 in Co-based bi-metal combinations (Co + V or Co + Fe) suggests the synergistic effect of doped metal ions owing to the heterogeneous near -neighbor environment. The present results are attributed to the surface heterogeneity between the host and the dopants, which selectively promotes methane activation as well as C-C coupling. This indicates a large scope to tune the activity of partial oxidation of methane and product selectivity with different metal-ion(s) combinations.

Sustainable CO2 reduction on in (2)O(3 )with exclusive CO selectivity: catalysis and in situ valence band photoelectron spectral investigations - Mhamane, Nitin B.; Chetry, Sibo; Ranjan, Ravi; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2022)
This study demonstrates a sustainable catalytic CO2 conversion to near 100% CO selectivity at ambient pressure on In2O3. Critically, high CO yield could be observed at the cost of undesired methanation, using a lower than stoichiometric amount of hydrogen in the feed; 1:1 and 1:0.67 CO2:H-2 ratios exhibit 98-99.6% CO selectivity with 25-38% CO2 conversion between 773 and 873 K. CO2 and H-2 conversion under steady-state conditions at 773-873 K suggests a 1:1 ratio of adsorbed reactants (with 1:0.67 CO2:H-2 feed) on the catalyst surface, underscoring the presence of an ideal reactant composition for the reverse water-gas shift reaction, while H-2-rich feed compositions show the H-2-dominated surface. Surface electronic structure changes, under near-operating conditions, were explored with near ambient pressure photoelectron spectroscopy (NAPPES), and the interesting findings are as follows: (a) A shift in the valence band to lower binding energy, up to 0.6 eV, was observed because of electron filling at high temperatures. (b) An observation of heterogeneous nature of the catalyst surface under NAPPES measurement conditions is attributed to the generation of active oxygen vacancy (O-v) sites, which in turn changes the work function of In2O3. (c) The above changes are found to be reversible, when the reaction was stopped. Vibrational features of the reactant molecules were observed to be broadened in the active temperature window of the catalyst supporting the heterogeneous character of the catalyst surface because of dynamic O-v generation. By optimizing gas hourly space velocity, CO2:H-2 ratio, and reaction temperature, exclusive CO selectivity is possible with a H-2:CO2 ratio of similar to 0.67, which will avoid the product separation stage altogether, while minimizing the expensive H-2 in the reactant feed.
Keywords: heterogeneous catalysis; Oxygen vacancy; photoelectron spectroscopy; RWGS; Work function

Baby step in assembling and integrating the components of an artificial photosynthesis device with forced heterojunctions towards improved efficiency - Salgaonkar, Kranti N.; Bajpai, Himanshu; Mhamane, Nitin B.; Nalajala, Naresh; Chauhan, Inderjeet; Thakkar, Kavita; Joshi, Kavita; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2023)
How to achieve unassisted, economical, scalable, and sustainable artificial photosynthesis for liquid fuels/products with improved solar-to-fuel efficiency (STFE) to address a carbon-neutral economy remains a big question. To a large degree, the extent of charge separation at heterojunction interfaces and charge utilization determine the STFE. Towards this, BiVO3 is assembled from ionic-precursors into TiO2 pores, and integrated structurally and electronically with TiO2 on calcination as BiVO4 quantum dots (BVQDs). BVQDs in TiO2 (BVT) pores lead to an all-inorganic system with a sub-quadrillion number of heterojunctions in a 1 cm(2) device (contains similar to 25 mu g of BiVO4 (similar to 2.5 wt%) in the nanopores of similar to 975 mu g of TiO2 (similar to 97.5 wt%)) and facilitate artificial photosynthesis. We demonstrate 31-38% STFE with a photon to chemical conversion turn over frequency (ToF(P2C)) of 2.73 s(-1) with a 1 cm(2) wireless BiVO4-TiO2 artificial leaf (BVT-AL) device for HCHO and CH3OH. The sequential nature of CO2 reduction to HCHO and then to CH3OH is evident from the reaction results. (CO2)-C-13 isotopic labeling experiments confirm that the input CO2 is the source for product formation. A large increase in the photocurrent density and incident photon-to-current efficiency (IPCE) of BVT, over 100% for the BiVO4 photoanode in visible light, demonstrates and supports efficient visible light absorption, charge separation and migration to the redox sites. A device has been demonstrated to show sustainable activity in direct sunlight, and addresses scalability from 1 to 9 cm(2). Assuming no change (50% decrease) in the STFE, a 6.74 m(2) device is expected to convert 1 (0.5) kg h(-1) CO2 into C1-oxygenates in sunlight. DFT calculations carried out with anatase TiO2 (101) and BiVO4 (121) interfaces support many of the experimental findings, including electron flow from the latter to the former, and interaction of the oxygen of TiO2 with BiVO4 and vice versa at the interface towards forced heterojunctions.

Co3O4 for sustainable CO2 reduction and possible fine-tuning towards selective CO production - Ranjan, Ravi; Tekawadia, Jyoti; Jain, Ruchi; Mhamane, Nitin B.; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2023)
Two main challenges involved in heterogeneous catalytic CO2 reduction are: (a) decreasing the consumption of H2 to the minimum required level with possibly the maximum CO2 conversion, and (b) concurrently enhancing the selectivity of the desired CO, at the cost of methane. Towards meeting these two challenges, Co3O4 spinel has been identified as a potential catalyst and it exhibits predominant CO selectivity > 673 K at atmospheric pressure. CO2 conversion begins > 523 K, with 100% CO selectivity observed > 673 K with CO2:H2 = 3:2. Current work shows a sustainable catalytic CO2 conversion to 100% CO selectivity with Co3O4-Nanocube (NC). Critically, CO selectivity and yield is observed to increase at the cost of methane with smaller amount of H2. 1:1 and 3:2 CO2:H2 ratio exhibits 88-100% CO selectivity with 24-32.5% CO2 conversion between 623 and 823 K. Irrespective of the input CO2:H2, ratio of CO2:H2 uptake changes from around 1:3 at 523 K to 1:1-1.5 at 823 K with concurrent production of significant methane to predominant CO, respectively. Surface electronic state changes was explored by near ambient pressure photoelectron spectroscopy, and the results suggests that Co3O4 is the active phase that promotes CO2 reduction selectively to CO. Broadening observed with the vibrational feature of the CO2 molecules at high temperature underscores the heterogeneous character of the catalyst surface, under operating conditions, due to changing electron density. By optimizing the gas hourly space velocity (GHSV), H2-lean CO2:H2 ratio, and the reaction temperature/pressure, 100% CO selectivity could be broadened to a range of operating conditions.
Keywords: Carbon neutral economy; heterogeneous catalysis; RWGS; SDG; Surface Science

Nanostructured Co-doped BiVO4 for efficient and sustainable photoelectrochemical chlorine evolution from simulated sea-water - Chauhan, Inderjeet; Patra, Kshirodra Kumar; Bajpai, Himanshu; Mhamane, Nitin B.; Salgaonkar, Kranti N.; Gopinath, Chinnakonda S. (Dalton Transactions, 2023)
The co-production of hydrogen and chlorine from sea-water splitting could be a potential, sustainable and attractive route by any method. However, challenges to overcome are many, and critically, the sustainability and operating potential of the electrocatalyst are important. In this work, we report on Co-doping in the BiVO4 (Co-BV) crystal lattice and employed the same as the photoanode; Co-BV exhibits a photocurrent of 190 mu A cm(-2) at 1.1 V vs. RHE (the reversible hydrogen electrode) in the acidic sodium chloride solution (pH 2.3) under one sun illumination. The best-performing photoanode, with 0.05 mol% of Co doping (0.05 Co-BV), selectively produced active chlorine with 92% faradaic efficiency at 1.1 V vs. RHE by successfully suppressing the kinetically sluggish oxygen evolution reaction (OER) and the stability of the catalyst was demonstrated for up to 20 h. This is the lowest operating potential reported for the chlorine evolution reaction (CER), thus far. The overpotential required for CER with 0.05 Co-BV is lower than that of OER, which leads to selective CER at 1.1 V (vs. RHE). Co-doping into the BiVO4 lattice decreases the charge transfer resistance and enhances the CER kinetics due to its structural and electronic integration with the BV lattice. We demonstrate that Co-doping also improves the lifetime of the charge carrier and enhances the current density of CER and sustainability of the catalyst.